Use of hyperdry amniotic membrane in operations for cleft palate: a study in rats. Issue 4 (April 2015) - Tsuno, Hiroaki; Noguchi, Makoto; Okabe, Motonori; Tomihara, Kei; Yoshida, Toshiko; Nikaido, Toshio
Abstract The growth of maxillary bone and the development of dentition are often impaired in patients who have had pushback operations for repair of a cleft palate. There has been considerable discussion about the most suitable technique or material used in such repairs to resolve the problem. Hyperdry amniotic membrane, a new preservable material derived from human amnion, has recently been introduced in several procedures. We have evaluated its use during pushback surgery in animal studies to try to correct the inhibition of growth and development of the maxilla. Mucosal defects were created in 3-week-old rats, and then covered with hyperdry amniotic membrane or not. Healing was assessed by histological and morphological examination at 1 week and 7 weeks postoperatively. In the group treated with hyperdry amniotic membrane, submucosal tissue was reconstructed successfully during the early postoperative period. Lateral palatal growth was not inhibited as much, and medial inclination of the teeth was less, after a period of growth using this material. The results suggest that hyperdry amniotic membrane is a suitable new dressing material for use in the treatment of cleft palate.